Extreme heat changes post‐heat wave community reassembly. Issue 11 (6th May 2015) - Seifert, Linda I.; Weithoff, Guntram; Vos, Matthijs
Abstract Climate forecasts project further increases in extremely high‐temperature events. These present threats to biodiversity, as they promote population declines and local species extinctions. This implies that ecological communities will need to rely more strongly on recovery processes, such as recolonization from a meta‐community context. It is poorly understood how differences in extreme event intensity change the outcome of subsequent community reassembly and if such extremes modify the biotic environment in ways that would prevent the successful re‐establishment of lost species. We studied replicated aquatic communities consisting of algae and herbivorous rotifers in a design that involved a control and two different heat wave intensity treatments (29°C and 39°C). Animal species that suffered heat‐induced extinction were subsequently re‐introduced at the same time and density, in each of the two treatments. The 39°C treatment led to community closure in all replicates, meaning that a previously successful herbivore species could not re‐establish itself in the postheat wave community. In contrast, such closure never occurred after a 29°C event. Heat wave intensity determined the number of herbivore extinctions and strongly affected algal relative abundances. Re‐introduced herbivore species were thus confronted with significantly different food environments. This ecological legacy generated by heat wave intensity led to differences in the failure or success of herbivore species re‐introductions. Reassembly was significantly more variable, and hence less predictable, after an extreme heat wave, and was more canalized after a moderate one. Our results pertain to relatively simple communities, but they suggest that ecological legacies introduced by extremely high‐temperature events may change subsequent ecological recovery and even prevent the successful re‐establishment of lost species. Knowing the processes promoting and preventing ecological recovery is crucial to the success of species re‐introduction programs and to our ability to restore ecosystems damaged by environmental extremes.